“It did not give me an option to decline”: a longitudinal analysis of the user experience of security and privacy in smart home products - Chalhoub, G; Kraemer, MJ; Nthala, N; Flechais, I (Association for Computing Machinery, 2021)
Smart home products aren’t living up to their promise. They claim to transform the way we live, providing convenience, energy efficiency, and safety. However, the reality is significantly less profound and often frustrating. This is particularly apparent in security and privacy experiences: powerlessness, confusion, and annoyance have all been reported.